2019
DOI: 10.1002/ijc.32738
|View full text |Cite
|
Sign up to set email alerts
|

Hair dye and chemical straightener use and breast cancer risk in a large US population of black and white women

Abstract: Many hair products contain endocrine-disrupting compounds and carcinogens potentially relevant to breast cancer. Products used predominately by black women may contain more hormonally-active compounds. In a national prospective cohort study, we examined the association between hair dye and chemical relaxer/straightener use and breast cancer risk by ethnicity. Sister Study participants (n = 46,709), women ages 35-74, were enrolled between 2003 and 2009, and had a sister with breast cancer but were breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
53
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 46 publications
6
53
0
Order By: Relevance
“…Interestingly, a recent US cohort study observed considerably higher breast cancer risk in black women and a borderline increased risk among white women who used permanent hair dyes,3738 which is largely consistent with our findings among US women with predominantly European ancestry. In particular, this recent study detected potential differences by estrogen receptor status; the risk associated with permanent hair dye appeared to be specifically increased for estrogen receptor negative breast cancer compared with estrogen receptor positive breast cancer 37. Our study, which was based on a larger number of women with breast cancer and more refined confounding control,39 observed similar findings for estrogen receptor negative breast cancers.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Interestingly, a recent US cohort study observed considerably higher breast cancer risk in black women and a borderline increased risk among white women who used permanent hair dyes,3738 which is largely consistent with our findings among US women with predominantly European ancestry. In particular, this recent study detected potential differences by estrogen receptor status; the risk associated with permanent hair dye appeared to be specifically increased for estrogen receptor negative breast cancer compared with estrogen receptor positive breast cancer 37. Our study, which was based on a larger number of women with breast cancer and more refined confounding control,39 observed similar findings for estrogen receptor negative breast cancers.…”
Section: Discussionsupporting
confidence: 91%
“…African Americans have higher risks of presenting with estrogen receptor negative and progesterone receptor negative breast cancer than non-Hispanic white people in the US 3536. Interestingly, a recent US cohort study observed considerably higher breast cancer risk in black women and a borderline increased risk among white women who used permanent hair dyes,3738 which is largely consistent with our findings among US women with predominantly European ancestry. In particular, this recent study detected potential differences by estrogen receptor status; the risk associated with permanent hair dye appeared to be specifically increased for estrogen receptor negative breast cancer compared with estrogen receptor positive breast cancer 37.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In Nigeria, Zheng and collaborators found 11.1% of women with breast cancer carried inherited genetic mutations in BRCA1 and BRCA2 , 49 while the prevalence is lower among women of European ancestry. Less established risk factors which are more prevalent among African women, such as the use of hair relaxers and dyes, 8,9 skin lighteners 8 as well as exposure to dichlorodiphenyltrichloroethane (DDT) (an endocrine modulator used for malaria control in many SSA countries), require more comprehensive studies across different African settings 7 …”
Section: Discussionmentioning
confidence: 99%
“…1,3 Data has demonstrated in vitro estrogenic and anti-estrogenic activity of these products, but further studies are warranted to investigate in vivo activity.3 Previous studies on the association between hair product use and breast cancer have shown inconsistent results; however, a large national prospective cohort study recently yielded significant results. 1,3,4 The study enrolled 50,888 participants with no history of breast cancer but had a sister with breast cancer. 4 The association between hair dye and chemical relaxer/straightener use and breast cancer risk was examined by ethnicity.…”
Section: Do Not Copy Penalties Applymentioning
confidence: 99%